Teologi Kesehatan dalam Fenomena Transgender dari Film The Danish Girl Sebagai Upaya Kesehatan Fisik dan Psikis - Sry Novita Tondang; Prionaray Bram M. (Institut Agama Kristen Negeri Toraja, 2026)
Abstract: The continuous advancement of technology has given rise to a strong theological voice in responding to these developments. In the world of health, biomedical developments have been quite rapid, specifically highlighting transgender issues facilitated by these technological advancements. This paper examines theology and popular culture in the film